Suicide prevention gatekeeper training in the Netherlands improves gatekeepers’ knowledge of suicide prevention and their confidence to discuss suicidality, an observational study - Terpstra, Sanne; Beekman, Aartjan; Abbing, Jens; Jaken, Sabine; Steendam, Martin; Gilissen, Renske (BMC public health, 2018)
Background The gatekeeper training is designed to help identify suicidal individuals, respond to suicidal ideation and refer to help. The internationally widely used training shows promising results. This is the first study presenting its effectiveness in the Netherlands and the first study investigating the effect in different employment sectors. Methods In an observational study, 113 Suicide Prevention – the Dutch suicide prevention expertise centre and lifeline - trained 526 professionals as gatekeepers. Changes in gatekeepers’ identifying and referral behaviour, knowledge of suicide prevention and skills-confidence were studied, using a pre-post (6 weeks after training) self-report questionnaire. Outcomes were analyzed with General Linear Model (GLM) repeated measures with four employment sectors (healthcare-, educational-, socioeconomic and other sectors) as a between-subjects factor. Results Pre-post self-reports of 174 respondents showed no change in the identification of suicidal people, referrals to the general practitioner (GP) or lifeline 113, but significant improvement in professionals’ knowledge and confidence ( p < .001). Results did not differ between employment sectors. Conclusions The gatekeeper training significantly increases suicide prevention knowledge and skills confidence in abilities to address suicidality. Healthcare, education, socioeconomic and other professionals (e.g. security, justice, transport, church workers) benefit similarly from the training. Increasing the number of gatekeeper training programs in all sectors is recommended.